Chromatographic Fingerprint Analysis of Herbal Medicines Thin-layer and High Performance Liquid Chromatography of Chinese Drugs - Wagner, Hildebert; Bauer, Rudolf; Melchart, Dieter; Xiao, Pei-Gen.; Staudinger, Anton; SpringerLink (Online service) (Vienna : Springer Vienna, 2011)
This manual, to be published in two volumes, provides a condensed overview of the analytical investigation of 80 Chinese Herbal Drugs which are most frequently in use. Thin layer chromatographic-, high pressure liquid chromatographic- and gas chromatographic-fingerprint analytical techniques allow the detection of all main low-molecular constituents of a plant drug and even single constituents can be visualized. Analytical results thereof are shown in numerous color figures. The quality proof of the investigation meets the standard of the European Drug Regulatory Authority. Furthermore, this volume gives a detailed description of the analytical methods used for several drugs. Bioactive constituents, pharmacological and biological activities of several single herbal drugs as well as their therapeutic applications are discussed.
Keywords: Medicine; Toxicology; Pharmaceutical technology; Biochemistry; Biomedicine; Pharmaceutical Sciences/Technology.; Pharmacology/Toxicology.; Plant Biochemistry